Quality of life and life satisfaction in former athletes: a systematic review and meta-analysis - Filbay, S; Pandya, T; Thomas, B; McKay, C; Adams, J; Arden, N (Springer, 2019)
Background: Sport participation has many physical and psychosocial benefits, but there is also an inherent risk of injury, subsequent osteoarthritis, and psychological challenges that can negatively impact quality of life (QOL). Considering the multifaceted impacts of sport participation on QOL across the lifespan, there is a need to consolidate and present the evidence on QOL in former sport participants. Objective: To evaluate QOL and life satisfaction in former sport participants, and determine what factors are associated with QOL and life satisfaction in this population. Methods: Eight electronic databases were systematically searched in 07/2018 to retrieve all articles that evaluated QOL or life satisfaction in former sport participants. Two authors independently screened titles/abstracts and full texts, extracted data and appraised methodological quality using a modified Downs and Black Checklist. Random effects meta-analysis estimated pooled mean and 95% CI for Mental Component Scores (MCS) and Physical Component Scores (PCS) derived from the SF-12, SF-36, VR-12 and VR-36 measures. MCS and PCS were pooled for all former sport participants, as well as professional- and collegiate-athlete subgroups. Data that were inappropriate for meta-analysis (i.e. EQ-5D, PROMIS and life-satisfaction outcomes) were collated and reported descriptively. Results: Seventeen articles evaluated QOL or life satisfaction in a total of 6692 former athletes (8 studies (n=4255) former professional athletes; 6 studies (n=1946) former collegiate athletes; 2 studies (n=491) included both) with a mean age ranging from 21-66 years. Most studies were cross-sectional (15 of 17 articles) and 12 studies had a moderate risk of bias (n=1 high-risk, n=4 low-risk). Unpublished data were provided for five studies. Meta-analysis of 7 studies resulted in a pooled PCS mean(95% CI) of 50.0(46.6 to 53.3) (former professional athletes from 2 studies: 46.7(42.1 to 51.2), former collegiate athletes from 5 studies: 51.2(48.4 to 53.9)) and a pooled MCS of 51.4(50.5 to 52.2) (former professional athletes: 52.7(51.3 to 54.2), former collegiate athletes: 50.9(50.0 to 51.8)). Factors associated with worse QOL or life satisfaction in former athletes included involuntary retirement from sport (3 studies), collision/high-contact sport compared with low/no-contact sport (3 studies), ≥3 concussions compared with no/fewer concussions (2 studies), increased BMI (worse PCS, 3 studies), and osteoarthritis or musculoskeletal issues (worse PCS and MCS, 3 studies; worse PCS but not MCS, 2 studies). Conclusions: Former athletes had similar PCS and better MCS, compared to general-population norms. Former athletes with impaired PCS reported better MCS than population norms, highlighting the need to use an instrument that differentiates between physical and mental components of QOL in former sport participants. Factors associated with worse QOL that may explain between-study variation include involuntary retirement, collision/high contact sports, concussion, BMI and osteoarthritis.